1979
DOI: 10.1210/jcem-49-4-543
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Uptake by the Parathyroid Glands

Abstract: Aluminum-containing drugs are used extensively to bind dietary phosphate and as antacids, but little is known about toxicity and tissue uptake of ingested aluminum. Aluminum concentrations were measured by neutron activation analysis in tissues taken from hyperparathyroid and normal human subjects and from rats. The parathyroid glands contained significantly more aluminum per unit mass than did thyroid or cervical muscle. The concentration of aluminum in the parathyroids appears to be linearly related to dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(20 citation statements)
references
References 6 publications
0
19
0
1
Order By: Relevance
“…It has been suggested that impaired parathyroid hormone secretion may explain this state of low bone formation. Aluminum may accumulate in parathyroid tissue (26), and Morrissey et al ( 17) have shown that aluminum reduces the secretion of iPTH from dispersed bovine parathyroid cells in vitro. The present results demonstrate that bone formation and apposition decrease early in the course of aluminum administration without concomitant reductions in the serum levels of iPTH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that impaired parathyroid hormone secretion may explain this state of low bone formation. Aluminum may accumulate in parathyroid tissue (26), and Morrissey et al ( 17) have shown that aluminum reduces the secretion of iPTH from dispersed bovine parathyroid cells in vitro. The present results demonstrate that bone formation and apposition decrease early in the course of aluminum administration without concomitant reductions in the serum levels of iPTH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a preliminary study reported that the PTH lev els in osteomalacic patients do not increase in response to hypocalcemia induced by low calcium dialysate [35], Thus, whether the low level of PTH results from parathy roidectomy or as part of the spontaneously occurring osteomalacic syndrome, the parathyroid axis may be defective and may contribute to the evolution of this syn drome. A potentially unifying element between alu minum and low levels of PTH is suggested by the report that aluminum is preferentially deposited in the parathy roid gland [36]. However, confirmation of these data is required and, in addition, proof that high parathyroid gland aluminum impairs production and/or secretion of PTH is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, aluminum accumulates in parathyroid glands and is known to inhibit their hormonal secretion. [27][28][29][30] We found no relation between the presence of aluminum deposits in bone biopsy specimens and the function of parathyroid subcutaneous grafts. This is in keeping with the results of Berland et al, 27 who found that the aluminum content of parathyroid glands was similar in patients with or without bone aluminum deposits and was only correlated with serum aluminum levels.…”
mentioning
confidence: 99%